SHOULD THE ACCOUNTING TEACHER PRACTICE ACCOUNTING? - van Voorhis, Robert H. (The Accounting Review, 1956)
Abstract To summarize briefly, it appears that the accounting teacher is usually pretty well occupied with teaching, counseling students, helping with administrative and committee work, directing graduate students in their projects, conducting research, writing, participating in the activities of his professional organizations, and taking part in his church and community affairs. The busy teacher may still feel a need for obtaining or continuing practical experience to keep him on his toes and abreast of current developments in accounting. He may be led into outside practice primarily for financial reasons. There are a variety of ways in which the teacher may practice. Those which permit him the fullest exercise of his learning and ability with the least routine or recurring procedures appear most likely to increase his effectiveness as a teacher, provided always that they are not too time-consuming in the aggregate. Those which involve repetitive book work seem more likely to dull his intellect. Accepting too much personal responsibility to clients may lead him to spend too much time and energy handling their work instead of performing his academic duties. This is particularly detrimental to his effectiveness as a teacher and should be avoided. Teachers and administrators should work together to develop a reasonable policy for their school concerning outside work. In conclusion, the answer to our question, "Should the accounting teacher practice accounting?" may be either "yes" or "no" depending on the circumstances. Practice should neither be required nor prohibited as a condition of employment. Arbitrary limitations should not be set on the type or amount of outside work an accounting teacher is permitted to do. Each assignment and the work of each teacher should be considered on its merits.